Integrating biomass and waste into high-pressure partial oxidation processes: Thermochemical and economic multi-objective optimization. (15th July 2022) - Rößger, Philip; Seidl, Ludwig Georg; Compart, Fred; Hußler, Johannes; Gräbner, Martin; Richter, Andreas
Abstract: The thermochemical conversion of biomass and waste represents an environmentally friendly concept for the production of fossil-based chemicals and even offers the possibility of a completely closed carbon cycle. This work investigates how biomass and waste can be integrated into the high-pressure partial oxidation process using their respective pyrolysis oils as feedstocks for methanol production. Different blends of light fuel oil and heavy fuel oil, biomass pyrolysis oil and waste pyrolysis oil are examined to investigate the transformation from fossil to renewable feedstocks. Technological, economic and environmental Pareto optimization using flowsheet modeling is applied to show how blend variations and the reactor's operating conditions affect gasification performance and total production costs. The results show that the optimal operating conditions of the reactor are directly related to the feedstock mixture. Different feedstock blends are optimal depending on the chosen objective functions. First, an economic Pareto optimization is performed for minimal operating expenditure and minimal capital expenditure. The Pareto front is dominated by designs that combine waste pyrolysis oil and heavy fuel oil, which is the most economically beneficial feedstock blend. Blending of biomass pyrolysis oil with heavy fuel oil results in minimal operating expenditure, and blending of waste pyrolysis oil and light fuel oil in minimal capital expenditure. Second, Pareto optimization is performed for minimal CO2 emissions and minimal methanol production costs. Here, the Pareto front is dominated by biomass pyrolysis oil, while minimal production costs are achieved in combination with heavy fuel oil. Lower CO2 emissions lead to higher total capital expenditure and production costs. Lastly, a sensitivity analysis revealed an effect of variable prices of CO2 and waste pyrolysis oil on the optimal feedstock blend and the reactor's operating condition. Graphical abstract: Image 1 Highlights: Partial oxidation of liquid hydrocarbons for methanol production is investigated. Process modeling with economic and environmental Pareto optimization is applied. Reactor operating conditions and blends of fossil and renewable oils are variated. Blending of biomass oil and heavy fuel oil lead to minimal operating expenditure. Blending of biomass pyrolysis oil and light fuel oil lead to minimal CO2 emissions.